Toegevoegde waarde in jaarverslae van Suid-Afrikaanse maatskappye: 'n Kort oorsig van die praktyk - A. P. Du Plessis (South African Journal of Business Management, 1987)
– South African listed companies (Johannesburg Stock Exchange, Industrial) have been following the example of British Companies since 1977 in the inclusion of a value-added statement in the annual report. An analysis of the statement of value added in the annual reports of 47 South African companies has shown that in respect of items like the title of the statement, the format, non-trading debits and credits, payroll costs, interest and dividends, taxation and retentions, a variety of practices are followed. The mere fact that information made available in the statement of value added is not standardized, complicates the task of interest groups such as shareholders, creditors, employees, financial analysts and others. This matter should receive the urgent attention of the Accounting Practices Board of the South African Institute of Chartered Accountants.
Keywords: 650